Global Change: Impacts on Water and food Security - Ringler, Claudia; Biswas, Asit K.; Cline, Sarah; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume examines the various drivers of global change, including climate change, and the use of agricultural knowledge, science, and technology, as well as the outcomes of global change processes, including impacts on water quality and human well-being. Several authors examine potential policy and institutional solutions afforded by globalization to the challenges ahead, particularly the role of trade policy. Financing water development in a more globalized world and adapting to global warming are also examined.
Water for Food Security Under Growing Scarcity -- Water and Food Security Under Global Change -- Global Water and Food Security: Megatrends and Emerging Issues -- Implications of Global Climatic Change on Water and Food Security -- Biofuels, Food Security, and the Environment: A 2020/2050 Perspective -- Trade for Water and Food Security-Help or Harm for the Poor? -- Implications of Globalization and Trade for Water Quality in Transboundary Rivers -- Failure of the Virtual Water Argument: Possible Explanations Using the Case Study of Mexico and NAFTA -- Globalization and Fisheries: Welfare Implications of Export Trade in Asia -- How to Finance Water for the Poor in a Globalized World -- Global Trends in Financing Water -- Private-Sector Participation in Water and Sanitation Services: The Answer to Public Sector Failures? -- Mobilizing Investment for Municipal Water Supply Services -- Water, Water Services and International Investment Agreements -- Conclusions -- Global Change: Options for Reform.
Keywords: Environmental sciences; Climatic changes; Environmental law; Sustainable development; Environmental pollution; Environment; Climate Change; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Environmental Law/Policy/Ecojustice.; Sustainable Development